Changes of Causative Organism and Antimicrobial Resistance in Urinary Tract Infections After the COVID-19 - Young Ho Choi; Jong Hyun Tae; Mi-Kyung Lee; Tae-Hyoung Kim (Urogenital Tract Infection)
Purpose During the coronavirus disease 2019 (COVID-19) pandemic, several studies reported changes in the distribution of microorganisms that cause major legal, respiratory, and gastrointestinal infectious diseases and increases in the antimicrobial resistance rates in Korea. On the other hand, there has been little domestic research on the causative organism of urinary tract infection (UTI). This study investigated the influence of the COVID-19 pandemic on the distribution of causative organisms and the antimicrobial resistance rate in UTI. Materials and Methods This study analyzed 17,201 urine cultures retrospectively from patients who visited Chung-Ang University Hospital from January 2018 to December 2021. Tests were then conducted to determine if there was a significant difference between the data for the eight quarters of the pre-COVID-19 period (January 2018 to December 2019) and the data for the eight quarters post-COVID-19 period (January 2020 to December 2021). Results Escherichia coli was the most common causative organism in all periods, but it decreased in the post-COVID-19 period. Enterococcus faecalis increased in the post-COVID-19 period. The ciprofloxacin resistance rate of E. coli and Klebsiella pneumoniae increased, but the ciprofloxacin and levofloxacin resistance rate of E. faecalis decreased. Conclusions There was little difference in the causative organism distribution of UTI and antimicrobial resistance rates before and after the COVID-19 pandemic. On the other hand, changes in some causative organisms are identified. Nevertheless, because this study was limited to a single medical institute, data from a broader spectrum of bacterial species collected from multiple institutions will be needed to obtain definitive results.